2013
DOI: 10.1007/s00248-013-0262-8
|View full text |Cite
|
Sign up to set email alerts
|

To What Extent Do Food Preferences Explain the Trophic Position of Heterotrophic and Mixotrophic Microbial Consumers in a Sphagnum Peatland?

Abstract: Although microorganisms are the primary drivers of biogeochemical cycles, the structure and functioning of microbial food webs are poorly studied. This is the case in Sphagnum peatlands, where microbial communities play a key role in the global carbon cycle. Here, we explored the structure of the microbial food web from a Sphagnum peatland by analyzing (1) the density and biomass of different microbial functional groups, (2) the natural stable isotope (δ 13 C and δ 15 N) signatures of key microbial consumers (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
75
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 60 publications
(89 citation statements)
references
References 58 publications
9
75
0
Order By: Relevance
“…This effect is particularly important in the spring and summer, when chironomid larvae attain their greatest abundance. Future research should also take into account the effect of meiofauna on the microorganism structure of the food web in peatland ecosystems, as literature data show that in some types of peatland this group can attain substantial numbers (Jassey et al 2013).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…This effect is particularly important in the spring and summer, when chironomid larvae attain their greatest abundance. Future research should also take into account the effect of meiofauna on the microorganism structure of the food web in peatland ecosystems, as literature data show that in some types of peatland this group can attain substantial numbers (Jassey et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The guts of chironomid larvae were mainly dominated by amoebae H. elegans and Nebela sp. As shown in a study by Jassey et al (2013), these species feed mainly on bacteria, ciliates, and other amoebae. Gilbert et al (2003) showed that Nebela tincta-type amoebae feed on a wide range of living, senescent, or dead microorganisms (fungi, microalgae, and other testate amoebae) and on organic remains.…”
Section: Predation Impact By Chironomid Larvaementioning
confidence: 95%
See 3 more Smart Citations